Understanding Emotional State on Female Correctional Officers in Java, Indonesia - Anggun Resdasari Prasetyo; Ika Zenita Ratnaningsih; Unika Prihatsanti (Journal of Educational, Health and Community Psychology, 2020)
Abstract Correctional institution has employees who are tasked with guarding inmates. High-risk job tasks that have to be faced by correctional officer can potentially affect the emotional state, moreover, if the officer is female gender. Based on the background, the study was aimed to know about the emotional state on female correctional officers. The research method used was clinical exploration by conducting in-depth interviews on 30 female correctional officers in Bandung and Semarang. The results can be concluded that the emotions experienced by the subjects in the study are mostly negative emotions. Negative emotions of anger, sadness, guilty, and anxiety is felt almost entirely by the 26 subject and only 4 subjects have positive emotional state, namely happiness and pride. From the data, there were 23 subjects who did positive emotion regulation, consist of 4 subjects who indeed were subjects who had positive emotional state and 19 subjects who initially had negative emotional state but were able to regulate emotions well. 19 of the 26 subjects who experienced negative emotional conditions tried to regulate positive emotions so that they could do a good job. Positive emotional regulations have been done by 23 subjects are positive reappraisal, refocus on planning, positive refocusing, and acceptance. The emotional regulation strategy used by 7 subjects was negative strategies, such as blaming other, self-blaming, and rumination or focus on thought. Keywords: Emotions at work, Correctional officer, Female.